Extending User Interface Design Patterns with accessibility recommendations to guide mobile developers - Casadei, Vitor (2018)
With the dissemination of mobile devices and the migration of activities that were once executed only on desktop computers to smartphones and tablets, the concerns related to accessibility in this environments have increased. Accessibility barriers can directly affect the access of information: a user with difficulties on accessing important information can become frustrated, absorbing the content with difficulty or even not being able to assimilate any information. The difficulties encountered by a great variety of users on mobile devices adds new challenges to the task of creating accessible applications for everyone. However, the accessibility impact of mobile interface design patterns in the life of disabled people has not been widely addressed in academic works. At the same time, the community of mobile designers and developers has made significant advances in identifying accessibility issues with design patterns on mobile interfaces, reporting these findings in virtual spaces of discussions as forums and blogs. Against this scenario, this project proposes recommendations that will help to mitigate or eliminate the accessibility barriers created by Interface Design Patterns on mobile applications. These recommendations were created based on two main studies. The first study was an accessibility evaluation based on interaction design patterns in an e-learning application containing 21 participants without disabilities that collected the emotional response to seven design patterns and video analysis using communicability metrics. While the second study aimed to explore the experiences and knowledge of professionals through an ethnographic study in 18 virtual communities of mobile design and development with the goal of identifying issues on the accessibility of Android mobile interface design patterns. This work presents two main contributions. It presents an approach to support the employment of virtual ethnography studies in software engineering as means to observe software development practice based on the information available in online communities. It also proposes 22 recommendations of 11 Interface Design Patterns and 11 Cross-section elements of mobile applications with the goal of improving the overall accessibility of mobile devices.